New Approach to Managing Onychophagia - O. Marouane; M. Ghorbel; M. Nahdi; A. Necibi; N. Douki (Hindawi Limited, 2016)
Onychophagia is defined as a chronic habit of biting nails, commonly observed in both children and young adults. This oral habit may lead to various medical and dental problems. To date, onychophagia is considered an unsolved problem in medicine and dentistry. In this paper we describe an exclusive nonpunitive fixed appliance utilizing a stainless steel twisted round wire bonded from canine to canine, in the mandibular arch, as a treatment of onychophagia. It was used successfully in young adult patients and maintained for a month. With 9-month follow-up the treatment has satisfied the patients' expectations which may eventually yield promising implications of this new treatment to similar situations.